Powerless science?: science and politics in a toxic world (The environment in history, volume 2) - Boudia, Soraya; Jas, Nathalie (The environment in history: international perspectives, 2014)
In spite of decades of research on toxicants, along with the growing role of scientific expertise in public policy and the unprecedented rise in the number of national and international institutions dealing with environmental health issues, problems surrounding contaminants and their effects on health have never appeared so important, sometimes to the point of appearing insurmountable. This calls for a reconsideration of the roles of scientific knowledge and expertise in the definition and management of toxic issues, which this book seeks to do. It looks at complex historical, social, and political dynamics, made up of public controversies, environmental and health crises, economic interests, and political responses, and demonstrates how and to what extent scientific knowledge about toxicants has been caught between scientific, economic, and political imperatives.